Party is over for EuropeEven. - Barber, Tony (World Today)
The author discusses the lack of economic growth in European countries as of 2012, compares the economic conditions in Europe to those in Japan in the 1990s, and argues that European nations are not as well positioned to adapt to those conditions. Topics include unemployment and "peripheral workers," property bubbles, and funding challenges for public health, education, and pension systems.